Symposium 3: Addressing Regulatory Issues Arising Within Cross-national, Collaborative eLearning Development Programmes - Windrum, Caroline; Crook, Charles (Proceedings of the International Conference on Networked Learning, 2006)
It is now widely accepted that all sectors of education will operate in increasingly regulated environments. The growth of eLearning provision in higher education presents an interesting challenge to the established frameworks and practices surrounding two of these areas: Quality Assurance and Intellectual Property Rights. Taken together, they present diverse demands upon those who wish to embark upon eLearning developments, particularly in cross-national, collaborative arenas. Using the example of the HEFCE funded eChina UK programme, we examine how regulatory issues were experienced by the designers, and consider the varieties of solution that they discovered for dealing with them. We also suggest an approach for thinking more creatively about the opportunities for usefully deploying regulatory considerations to aid the educational materials design process.